Field reports form for submitting seasonal observations of Iowa birds - Fuller, James L.et al (1985)
An annotated list of birds sighted by Jim Fuller. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed